Observing the Development of the As-Sunnah Islamic College: (Historical Studies) - Isnawati; Nunzairina; Muhammad Sapii Harahap (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2022)
The formulation of the problem in this research is how is the development of the As-Sunnah Islamic High School from 2002 to April 2022?” The purpose of this study is